Gender Prediction From Tweets With Convolutional Neural Networks: Notebook for Pan at Clef 2018 - Sezerer, Erhan; Tekir, Selma; Polatbilek, Ozan; Sevgili, Özge; Tekir, Selma; Sezerer, Erhan (CEUR Workshop Proceedings, 2018)
This paper presents a system1 developed for the author profiling task of PAN at CLEF 2018. The system utilizes style-based features to predict the gender information from the given tweets of each user. These features are automatically extracted by Convolutional Neural Networks (CNN). The system mainly depends on the idea that the informativeness of each tweet is not the same in terms of the gender of a user. Thus, the attention mechanism is included to the CNN outputs in order to discriminate the tweets carrying more information. Our architecture was able to obtain competitive results on three languages provided by the PAN 2018 author profiling challenge with an average accuracy of 75.1% on local runs and 70.23% on the submission run.
19th Working Notes of CLEF Conference and Labs of the Evaluation Forum, CLEF 2018; Avignon; France; 10 September 2018 through 14 September 2018
Keywords: Neural networks; Convolution; Convolutional Neural Networks